Repeatability of faecal egg-count and haematological values in sheep experimentally infected with Haemonchus contortus - SWARNKAR, C P; KHAN, F A; JAYASANKAR, J; SINGH, D; BHAGWAN, P S K (The Indian Journal of Animal Sciences, 2014)
Avivastra lambs (12) were experimentally infected twice with 10 000 infective larvae of Haemonchus con tontortus at 7-week interval. Another 6 lambs of same breed served as infectivity control and 4 lambs were healthy controls. The mean faecal egg count peaiced 6-7 wed(s atter both the infections. The mean packed-cefl volume decreased significantly from week 3 while, mean haemoglobin and total erythrocyte count dropped from week 5 onward. The repeatability of mean faecal egg count, haemoglobin, packed-cell volume, mean corpuscular haemoglobin concentration and body weight for each animal between 2 infections were 0.4958, 0.4899, 0.5509, 0.6098 and 0.9410 respectively. Worm burden and faecal egg count were negatively correlated with haemoglobin, packed-cell volume, total erythrocyte count and body weight. Multiple regression analysis revealed that 5 variables - faecal egg count, haemoglobin, packed-cell volumc, totul erythrocyte count and body weight - together accounted for 86% of the observed variation in worm burden among lambs. ft was concluded that under these controlled conditions these markers are reasonably appropriate for detecting the resistance status of sheep against H. contotus.